TERJEMAHAN KALIMAT PASIF BAHASA INDONESIA KE DALAM BAHASA JEPANG (STUDI PADA NOVEL LASKAR PELANGI DAN NIJI NO SHOUNEN TACHI) - Tiara Freshca Dewi S; Hana Nimashita; Zuli Laili Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study discusses the translation of Indonesian’s passive voice in the Laskar Pelangi into Japanese on a Niji No Shounen Tachi novel. The purpose of this study was to determine the form of the passive voice translation into Niji No Shounen Tachi Japanese novel and how to shift and modulation in the passive voice translation using Catford theory and Newmark in Machali. The object of research is passive voice on Laskar Pelangi and Niji No Shounen Tachi novel. This research is a qualitative descriptive method. Results of the study found that passive voice translation is not always translated as passive voice in the target language. In this study found few differences in meaning in the Indonesia’s passive voice translation into Japanese so that shifting, but the message conveyed in Indonesian into Japanese translation.Keyword: Translation, Passive Sentences, Novel, Laskar Pelangi, Niji No Shounen Tachi